2019 EULAR points to consider for non-physician health professionals to prevent and manage fragility fractures in adults 50 years or older. Issue 1 (24th April 2020) - Adams, Jo; Wilson, Nicky; Hurkmans, Emalie; Bakkers, Margot; Balážová, Petra; Baxter, Mark; Blavnsfeldt, Anne-Birgitte; Briot, Karine; Chiari, Catharina; Cooper, Cyrus; Dragoi, Razvan Gabriel; Gäbler, Gabriele; et al.
Abstract : Objective: To establish European League Against Rheumatism (EULAR) points to consider for non-physician health professionals to prevent and manage fragility fractures in adults 50 years or older. Methods: Points to consider were developed in accordance with EULAR standard operating procedures for EULAR-endorsed recommendations, led by an international multidisciplinary task force, including patient research partners and different health professionals from 10 European countries. Level of evidence and strength of recommendation were determined for each point to consider, and the mean level of agreement among the task force members was calculated. Results: Two overarching principles and seven points to consider were formulated based on scientific evidence and the expert opinion of the task force. The two overarching principles focus on shared decisions between patients and non-physician health professionals and involvement of different non-physician health professionals in prevention and management of fragility fractures. Four points to consider relate to prevention: identification of patients at risk of fracture, fall risk evaluation, multicomponent interventions to prevent primary fracture and discouragement of smoking and overuse of alcohol. The remaining three focus on management of fragility fractures: exercise and nutritional interventions, the organisation and coordination of multidisciplinary services for post-fracture models of care and adherence to anti-osteoporosis medicines. The mean level of agreement among the task force for the overarching principles and the points to consider ranged between 8.4 and 9.6. Conclusion: These first EULAR points to consider for non-physician health professionals to prevent and manage fragility fractures in adults 50 years or older serve to guide healthcare practice and education.